An energy-saving pumping system with novel springs energy storage devices: Design, modeling, and experiment. (January 2017) - Meng, Hong jun; Quan, Long; Wang, Zhanlin; Wang, Cheng wen; Lan, Yuan
For the traditional reciprocating pumping unit, it generally starts at the bottom dead point with full load and is accelerated when starting and decelerated when stopping, which not only requires great energy from the motor but also impact on the output torque of motor. In order to tackle the above problems, we propose an energy-saving smooth reversing pumping system, which could store the energy in deceleration by making use of springs, and the stored energy could be reused in acceleration after reversion. This novel system targets to make the motor starting with light load, which could reduce the fluctuation in motor torque, decrease the starting time. In this article, a dynamic model and an efficiency model are established to compute the polished rod load dynamometer card and efficiency of the pumping unit. It is shown that the installed springs could help to reduce the impact on the system when reversing, and significantly decrease the energy consumption. In addition, we set up the real pumping system with load test system to verify the effectiveness of the model establishment. Through the experiment, the proposed pumping system could save energy up to 9.204% as compared to the traditional reciprocating pumping system.